The Influence of Taqwa (Piety) and Amal Saleh (Good Deeds) on Patience Among Muslim Students at an Islamic Campus - Ahmad Hidayat; Muhammad Azhar; Halim Purnomo; Iredho Fani Reza; Lisfarika Napitupulu (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
There are situations that require patience for Muslim students, such as patience in following the commands and prohibitions of Allah SWT, which is also referred to as patience in piety. Additionally, Muslim students need to exercise patience in maintaining their relationship with Allah SWT and fellow living beings, known as patience in performing good deeds. The purpose of this research is to investigate the influence of piety and good deeds on patience among Muslim students in an Islamic campus. The participants involved in this study were 227 Muslim students enrolled in the Faculty of Psychology at the Islamic University of Riau. Convenient sampling was employed for data collection. The data were gathered using the patience scale, good deeds scale, and piety scale. Partial Least Square (PLS) analysis was conducted using smart PLS 3.0 M3 software. The findings of this research indicate that piety has a positive and significant influence on patience among Muslim students in an Islamic campus, while good deeds do not have a significant influence and are discussed as a limitation of this study. The implications of this research provide new empirical support regarding factors influencing patience, specifically the variable of piety.